A rare human variant that disrupts GPR10 signalling causes weight gain in mice - Fleur Talbot; Claire H. Feetham; Jacek Mokrosiński; Katherine Lawler; Julia M. Keogh; Elana Henning; Edson Mendes de Oliveira; Vikram Ayinampudi; Sadia Saeed; Amélie Bonnefond; Mohammed Arslan; Giles S. H. Yeo; et al. (Nature Communications, 2023)
The brain-expressed receptor GPR10 is involved in energy homeostasis in mice. Here the authors identify rare loss of function variants in GPR10 in people with severe obesity and showed that one of these variants causes obesity when modelled in mice, suggesting that future studies could explore GPR10 as a potential target for weight-loss therapy.